Synthesis and Cytotoxicity of Chalcones and 5-Deoxyflavonoids - Jing Zhang; Xin-Ling Fu; Nan Yang; Qiu-An Wang (The Scientific World Journal)
Chalcones 1~8 and 5-deoxyflavonoids 9~22 were synthesized in good yields by aldol condensation, Algar-Flynn-Oyamada reaction, glycosidation, and deacetylation reaction, respectively, starting from 2-acetyl phenols substituted by methoxy or methoxymethoxy group and appropriately benzaldehydes substituted by methoxy, methoxymethoxy group, or chlorine. Among them, 13 and 17~22 are new compounds. The cytotoxicity bioassays of these chalcones and 5-deoxyflavonoids were screened using the sulforhodamine B (SRB) protein staining method, and the results showed that compounds 2, 4, 5, 6, 10, 15, and 19 exhibited moderate cytotoxicity against the cancer cell line of MDA-MB-231, U251, BGC-823, and B16 in comparison with control drugs (HCPT, Vincristine, and Taxol).